A versatile cell line for establishing potency of cell type-specific AAV transgenes - Refugio A. Martinez; Yemeserach M. Bishaw; Meagan A. Quinlan; Erin L. Groce; Bryan B. Gore; Ed S. Lein; John K. Mich; Boaz P. Levi (Molecular Therapy: Methods & Clinical Development)
Potency assays are essential for adeno-associated virus (AAV) therapy development, allowing simple and quantitative assessments of therapeutic activity, target engagement, vector stability, and activity per batch. However, cell culture-based AAV potency assays are generally hampered by two limitations: (1) commonly used cell lines have low AAV transduction efficiency due to their lack of appropriate surface receptors, and (2) cell type-specific AAV transgenes are often not expressed because their regulatory elements (enhancers, promoters, etc.) may not be active in the cell lines used for testing. Here, we present the CRISPR activation-AAV receptor (CRAAVR) cell line, a stable HEK293T-derived line that overcomes both problems. CRAAVR cells constitutively express the AAV receptor (AAVR) and an AAV-targeted CRISPR transactivator, and, as a result, exhibit high transduction efficiency and drive transgene expression from AAVs with cell type-specific regulatory elements. Furthermore, CRAAVR cells can assess AAV transgene potency in a quantitative manner, as demonstrated by gamma-aminobutyric acid (GABA) uptake of an AAV-delivered GABA transporter (GAT-3). Due to their greater transduction efficiency, regulatory element-agnostic expression, and utility as a potency assay tool, CRAAVR cells will help streamline the development and validation of AAV-based reagents and therapeutics.